Health Knowledge for Iraqi Women and Social Media - et. al., Hind Nadhim Kazar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research deals with the importance of the role social media play, and the topic of the research revolves around the extent to which Iraqi women depend on social media as an element of health information. The research questions are embodied about what are the reasons for the use of the Iraqi time on social media? And what social media do women use in Iraq ? that the research clarifies the health information that social have focused on, how to study them, and the persuasive methods used to suit the nature of the target group. Identifying the extent to which ethnic women depend on Facebook as a source for obtaining health information, and the research concluded that the interest and integration of women in modern communication technology and their dependence on the Internet was greatly, and that one of the most important reasons for the Iraqi reliance on websites in the acquisition of health information is ease access to information, because a large percentage of them own smart phone.